The Effect of Family Clean and Healthy Living Behavior Education (PHBS) on the Prevention of Diarrhea in Toddlers - Yasin, Zakiyah; Nawawi, Ahmad; Rukmini Devy, Shrimarti; Rahayu Nadhiroh, Siti (Universitas Airlangga, 2025)
Background: Diarrhea is a public health problem that is experienced by many developing countries such as Indonesia, because there are still many people who do not implement PHBS (Clean and Healthy Living Behavior) properly so that the incidence of diarrhea in toddlers is still a potential Extraordinary Event (KLB) which is very often accompanied by death. Objectives: The purpose of the study was to determine the effect of family PHBS education on the prevention of diarrhea in toddlers in Ambunten District, Sumenep Regency. Methods: This study is a quantitative study with a quasi experimental design. The population in this study is mothers who have toddlers under 5 years old. The sample of 66 respondents uses a random sampling technique is obtained. Data was collected using a diarrhea prevention questionnaire. Results: The results of the study before being given education to the treatment group and control group were mostly sufficient. Results: The results of the study after being educated in the treatment group and control group were good with the number of p value = 0.000 which means that there is an effect of family PHBS education on the prevention of diarrhea in toddlers under 5 years old in Ambunten District, Sumenep Regency. Conclusion: Health workers can provide counseling about household PHBS to mothers who have toddlers under 5 years old, so that they can apply PHBS properly and correctly in order to reduce the mortality rate in toddlers caused by diarrhea.